2018
DOI: 10.1001/jamaoncol.2017.2391
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Toxic Effects and Time to Treatment Failure for Nivolumab Plus Ipilimumab in Melanoma

Abstract: We observed a 91% incidence of clinically significant immune-related AEs leading to frequent emergency department visits, hospitalizations, and systemic immunosuppression. Immuno-oncology trials should routinely report these metrics. Most patients do not tolerate 4 doses of nivo + ipi; however, 4 doses may not be required for clinical benefit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
119
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 139 publications
(124 citation statements)
references
References 8 publications
2
119
0
3
Order By: Relevance
“…Finally, the endpoint was TTF, which is slightly more subjective than the more commonly reported PFS or overall response rate (ORR). Indeed, PFS or ORR would be preferred measures of treatment efficacy in the prospective setting, but retrospective assessment of these outcomes is fraught with challenges, especially when Response Evaluation Criteria for Solid Tumors (RECIST)‐defined or Immune‐Related RECIST (irRECIST)‐defined progression are not recorded, as in our institutional database . Other studies have found that the baseline NLR was associated with PFS and/or ORR in patients with melanoma who received treatment with a checkpoint inhibitor, but it remains to be determined whether a change in the NLR during treatment would be similarly associated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the endpoint was TTF, which is slightly more subjective than the more commonly reported PFS or overall response rate (ORR). Indeed, PFS or ORR would be preferred measures of treatment efficacy in the prospective setting, but retrospective assessment of these outcomes is fraught with challenges, especially when Response Evaluation Criteria for Solid Tumors (RECIST)‐defined or Immune‐Related RECIST (irRECIST)‐defined progression are not recorded, as in our institutional database . Other studies have found that the baseline NLR was associated with PFS and/or ORR in patients with melanoma who received treatment with a checkpoint inhibitor, but it remains to be determined whether a change in the NLR during treatment would be similarly associated.…”
Section: Discussionmentioning
confidence: 99%
“…OS was the primary outcome and was calculated from the date of the first dose of PD‐1 inhibitor monotherapy until death or the date of last follow‐up. The time to treatment failure (TTF) was defined as the interval between the date of the first dose of PD‐1 inhibitor and the earliest occurrence of either clinical progression, initiation of new therapy (local or systemic), or death …”
Section: Methodsmentioning
confidence: 99%
“…7,8 This is in contrast to cytotoxic T-lymphocyte-associated protein 4 (CTLA-4) receptor occupancy, which is believed to last on the order of several weeks. 7,8 This is in contrast to cytotoxic T-lymphocyte-associated protein 4 (CTLA-4) receptor occupancy, which is believed to last on the order of several weeks.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, existing data also indicate a marked increase in the risk of serious treatment-related side effects associated with such drug combination approaches [1-3]. …”
mentioning
confidence: 99%
“…Centers with considerable experience dealing with the side effects associated with the delivery of combination checkpoint inhibitors have noted a high risk of serious toxicity, including required hospitalizations and emergency room visits [3]. However, it can be anticipated that when patients are treated in the real-world setting outside the realm of clinical trials (e.g., older patients, patients with existing clinically relevant comorbidities, etc.)…”
mentioning
confidence: 99%